Pengaruh Citra Merek, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk UMKM Jenang Krasikan Bunga Kamboja Sukoharjo - Nur Affandi, Muhammad; Susanti, Retno (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to identify and evaluate the effect of brand image, product quality, and price perception on consumer purchasing decisions at Jenang Krasikan Bunga Kamboja Micro, Small and Medium Enterprises (MSMEs) in Sukoharjo. The research method used is a survey with a quantitative approach, relying on primary data obtained from 100 respondents of these MSME customers. The sampling technique applied was accidental sampling. Data collection was carried out through distributing questionnaires, in-depth interviews, and documentation. The questionnaire instrument has been tested for validity and reliability. Data analysis includes classical assumption tests (multicollinearity, autocorrelation, heteroscedasticity, and normality) and multiple linear regression analysis to test the effect of independent variables on the dependent variable. In addition, the t-test, F-test, and coefficient of determination test were also conducted to measure the significance of the model and its predictive power. The t-test analysis indicates that brand image does not have a significant influence on consumer purchasing decisions. In contrast, product quality was identified as a factor that significantly influenced purchasing decisions. Meanwhile, the price variable did not show a significant influence on purchasing decisions